3d transition metal doping-induced electronic structures and magnetism in 1T-HfSe2 monolayers. Issue 83 (14th November 2017) - Zhao, Xu; Yang, Congxia; Wang, Tianxing; Ma, Xu; Wei, Shuyi; Xia, Congxin
Abstract : By performing first-principles calculations, we explore the structural, electronic and magnetic properties of 3d transition metal (TM) atom-doped 1T-HfSe2 monolayers. Abstract : By performing first-principles calculations, we explore the structural, electronic and magnetic properties of 3d transition metal (TM) atom-doped 1T-HfSe2 monolayers. The results show that it is energetically favorable and relatively easier to incorporate 3d TM atoms into the HfSe2 under Se-rich experimental conditions. Electronic structures and magnetism can be tuned effectively for V, Cr, Mn, Fe, and Cu doping. We find that the V, Cr, Mn, Fe impurity atoms prefer to stay together in the nearest neighboring (NN) configuration and show ferromagnetism (FM) coupling. Moreover, V-doped HfSe2 shows the characteristics of FM half-metallic properties, and it has lower formation energy. The strong p–d hybridization mechanism is used to explain the magnetism of TM-doped HfSe2 structures. Thus, we can conclude that 3d TM doping can induce the change of electronic structures and magnetism of 1T-HfSe2 monolayers, which is important for applications in semiconductor spintronics.